2016
DOI: 10.3126/ijssm.v3i4.15973
|View full text |Cite
|
Sign up to set email alerts
|

Gap Analysis of Employability Skills of Entry Level Business Graduates Based on Job-Fit Theory

Abstract: This paper analyzes the perceptions of the employer on how job fit is fresh business school graduates in the Indian business scenario. The responses of employers on skills considered in the recruitment of management graduates, matching to their business profile as well as job profiles, were compared with the actual skill set of fresh MBAs inducted from the higher education sector. This study also investigated the level of importance of skills required by a new business graduate from the employer's expectations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…It means that the prospective teachers were not achieved the competences whatever they desired from the programme. The results of various studies (Hakim & Bizri, 2015;Junior, 2014;Metilda & Neena, 2016;Parvaiz, 2014;Shah et al, 2017;Siddoo, Sawattawee, Janchai, & Yodmongkol, 2017a;Subramonian, 2008) were found aligned with that of the present study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It means that the prospective teachers were not achieved the competences whatever they desired from the programme. The results of various studies (Hakim & Bizri, 2015;Junior, 2014;Metilda & Neena, 2016;Parvaiz, 2014;Shah et al, 2017;Siddoo, Sawattawee, Janchai, & Yodmongkol, 2017a;Subramonian, 2008) were found aligned with that of the present study.…”
Section: Discussionsupporting
confidence: 90%
“…The aforementioned gaps signified the fact that there was less mutual interaction between employers and the teachers. Metilda and Neena (2016) analyzed desire-achievement gap regarding generic competences in the perception of Indian business graduates. Higher gap was found in desire-achievement employability competences of Business graduates.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, a skills gap analysis was performed to identify the gaps between the employer's expected skills (required) and the actual skills possessed by graduates (acquired) (Metilda & Neena, 2016). Skills gap analysis provides a mechanism to identify skills that are lacking among the interns through an evaluation performed by their employers during internship.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous jobs which were formerly undertaken by people are nowadays carried out by machines, primarily due to the rise of automation and artificial intelligence. This means that people must constantly acquire new skills and knowledge to be viable in the job market (Metilda & Neena, 2017). Furthermore, the COVID-19 pandemic has hastened the transition towards remote employment, making digital skills more crucial than ever (Hettiarachchi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%